PENGELOLAAN BANK PLASTIK DALAM UPAYA PENINGKATAN EKONOMI DAN KEBERSIHAN DI DESA WISATA CEPAKA - Ni Nyoman Sri Rahayu Trisna Dewi; Tiara Kusuma Dewi (Universitas Triatma Mulya, 2021)
Garbage is a major problem in the community which can cause environmental pollution, the daily life of the village community is more about processing the final waste by burning it at a certain time, therefore with the existence of a waste bank there will be an increase in environmental awareness and perhaps economic awareness. The Garbage Bank is a business entity engaged in inorganic waste management. People can sort and save waste at the Garbage Bank, so that it can generate economic value. The Garbage Bank serves customers in saving waste, but most of the Garbage Bank still uses conventional transaction facilities, which causes the transaction data to be lost, damaged, or inaccurate calculation of transaction data. The Garbage Bank also serves garbage collection to customer locations around the Garbage Bank. This research has the main objective to provide assistance in the making and provision of administrative bookkeeping to the Management of the Cepaka Harum Plastic Bank.